019 Improving the quality of ambulance crew hand-overs: a qualitive study of knowledge transfer in emergency care teams. Issue 3 (1st March 2011) - Murray, Steve; Crouch, Robert; Pope, Catherine; Lattimer, Val; Thompson, Fizz; Deakin, Charles; Ainsworth-Smith, Mark
Abstract : Introduction: Ambulance crews make 3.6 million emergency journeys each year. Effective patient transfer relies on verbal, non-verbal and documentary handover of complex information in time-limited environments. Weaknesses in ambulance handover have been noted but little work has been done to investigate the process and identify good practice. Research has looked at communication during transfer of care; standardised resuscitation handover formats have been used but do not always improve accuracy. Ineffective handover threatens patient safety, quality and efficiency of care. This study provides an in-depth examination of handover to inform practice and education. Method: We are conducting an ethnographic case study of handover in an ambulance Trust. Researchers are accompanying crews as they undertake their day-to-day work, using observation and video-recording to capture handover—from data collection at scene, pre-alerting (by radio, telephone and computer) through to the hospital. We are also collecting information from patient records along with training materials, policies and directives pertaining to handover. Ethnography allows for informal conversations to take place as appropriate during the fieldwork to clarify understandings and explore emerging themes in the analysis. In addition we are using semi-structured interviews with patients, carers, ambulance staff, nurses, doctors and non-clinical hospital staff to explore the handover process. Result: The project started 2nd April 2009. This poster will outline the methodology, present some of the emerging themes from our analysis and describe future data collection and analysis plans. Discussion: This is an ongoing project. We will present our experience of undertaking this unusual project—especially issues surrounding accessing staff and the practicalities of data collection. By presenting this work we seek to inform future research into emergency care.